THE POTENTIAL ROLE OF HOUSING UNIT DIVERSITY IN GATED COMMUNITIES IN SOCIAL COHESION - HASAN , HAIDER MAJID; AHMED , HUSSEIN ISMAEL; ABED, NISREEN KHALIL; ABED, ALYAA RAZZAQ; A-HUSSEIN, SHAHAD ABD; DASHAR , AHMED JAMEEL (Journal of Duhok University, 2023)
Perhaps the new gated communities are good examples of urban design in their own right, and the questions that the paper raises are how the diversity of housing unit space affects social cohesion and how we can design communities to increase social cohesion among its occupants in the future. The diversity of land uses facilitates better social cohesion s and bonds, as good street coordination and open spaces calming traffic contribute to creating a suitable built environment for residents to generate a sense of place. Gated residential compound models seek to create residential units that provide a safe, luxurious and private life for its residents. They achieved it simply by gated themselves. Studies have confirmed that the main reason that prompted investors to build gated communities is their desire to achieve quick wealth and that the diversity in the area of ​​the residential unit in it contributed well to the speed of marketing the residential units built in it, so this research paper seeks to show the effect of the diversity of the area of ​​the residential unit on the efficiency Residential use in gated communities. The research concluded that the gated community has achieved a state of balance in residential use through the diversity of housing units.